KEMISKINAN SEBAGAI KOMODITAS MEDIA (Analisis Strategi Komunikator dalam Program Berita Bertema Kemiskinan di Televisi) - Ri'aeni, Ida (SEMIOTIKA: Jurnal Komunikasi, 2014)
Poverty has a broad meaning, depending on which our perspective and interpreted. It could be interpreted broadly when people can’t meet basic needs such as food, clothing, and shelter. Poverty has two bad consequences that undermine the dignity of those affected. First, poverty means that basic needs of the poor as human beings and as members of society are not met. Secondly, poverty resulting in total dependence of the poor of the willingness of people and other groups.In some mass media, themed program shows that poverty is the bestseller watchable and succesfull to influence feeling of the audience. However, the spectacle seems to inspirepeople just play, not showing the solution of the problem of poverty.  Keywords: Television Programme, Poverty, Development Journalism, Communicators.